2000
DOI: 10.1063/1.1290008
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional study of intramolecular ferromagnetic interaction through m-phenylene coupling unit (II): Examination of functional dependence

Abstract: As a first step toward examination of ferromagnetic polymers and dendrimers by ab initio crystal orbital methods, we elucidated candidates for monomer units with the high-spin ground states in the previous study of Part I [J. Chem. Phys. 113, 4035 (2000)] by employing density-functional (DFT) methods using Becke’s and Becke’s three parameter exchanges with Lee–Yang–Parr correlation or Hartree–Fock (HF) molecular orbital and post HF approximations. However, it was found that further computations applying other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 72 publications
3
66
0
Order By: Relevance
“…[26][27][28][29][30] In all of these calculations, the triplet states were consistently below the energy of the singlets. This would imply that the magnetic interaction between two dimers should be ferromagnetic.…”
Section: Unexpected Magnetic Properties Of La 3 Re 2 O 10mentioning
confidence: 99%
“…[26][27][28][29][30] In all of these calculations, the triplet states were consistently below the energy of the singlets. This would imply that the magnetic interaction between two dimers should be ferromagnetic.…”
Section: Unexpected Magnetic Properties Of La 3 Re 2 O 10mentioning
confidence: 99%
“…All other factors being equal, 28 polarization of unpaired spin density toward (or away) from the ligating atoms will increase (or decrease) the magnitude of electronic coupling. The notion of altering the magnetic properties of molecules through chemical means has been addressed both computationally [29][30][31][32] and experimentally. [33][34][35] Recent work by Shultz and co-workers, in particular, has clearly demonstrated that spin delocalization contributes to the attenuation of exchange interactions in bridged polynuclear systems.…”
Section: Introductionmentioning
confidence: 99%
“…Judging from many other examples, [17][18][19][20][21] this tendency is reasonable. On the other hand, the potential energies for the HS state of 1 were shown in Figure 4B.…”
Section: A Thoretical Background (I) Magnetic Ringsmentioning
confidence: 99%
“…Here, we first examine ab initio spin Hamiltonian model for moleculebased magnets, where the effective exchange interactions are determined by the first-principle broken-symmetry (BS) density functional calculations. 17,18 As an example, the BS DFT calculations of a magnetic ring consisted of 34 hydrogen atoms is performed to determine the potential energy curves of the lowest -and highest-spin states of the species, and the effective exchange integrals are calculated by the energy difference between them. The natural orbital analysis of the BS DFT solutions is also carried out to obtain symmetry-adapted (SA) natural molecular mobitals (MO) and their occupation numbers.…”
Section: Introductionmentioning
confidence: 99%